Molecular characterization of diarrheagenic Escherichia coli isolates from children with diarrhea: A cross-sectional study in four provinces of Mozambique: Diarrheagenic Escherichia coli in Mozambique. (August 2022) - Manhique-Coutinho, Lena; Chiani, Paola; Michelacci, Valeria; Taviani, Elisa; Bauhofer, Adilson Fernando Loforte; Chissaque, Assucênio; Cossa-Moiane, Idalécia; Sambo, Júlia; Chilaúle, Jorfélia; Guimarães, Esperança Lourenço; Salência, Judite; Cassocera, Marta; et al.
Highlights: ****Diarrheagenic Escherichia coli were identified in children in Mozambique. Enteroaggregative E. coli was the most frequently detected pathotype. Detection of virulence genes of multiple diarrheagenic E. coli was observed. High frequency of resistance to ampicillin and tetracycline was observed. ABSTRACT: Objectives: Analyze the frequency of diarrheagenic Escherichia coli (DEC) pathotypes and their antimicrobial resistance profiles among children aged <15 years with diarrhea in four Mozambican provinces. Methods: A cross-sectional hospital-based surveillance program of diarrhea was implemented in Maputo, Sofala, Zambézia, and Nampula. A single stool sample was collected from each child from May 2014 to May 2017. Culture methods and biochemical characterization were performed to detect E. coli strains. DEC pathotypes were determined by conventional polymerase chain reaction targeting specific virulence genes. Antimicrobial susceptibility was assessed by the Kirby–Bauer method. Results: From 723 specimens analyzed by culture, 262 were positive for E. coli . A total of 208 samples were tested by polymerase chain reaction for DEC identification, of which 101 (48.6%) were positive for a DEC pathotype. The predominant pathotypes were enteroaggregative (66.3%, 67/101), enteropathogenic (15.8%, 16/101), enterotoxigenic (13.9%, 14/101), and enteroinvasive E. coli ( 4.0%, 4/101). No Shiga toxin–producing E. coli was identified. Regardless of the province, the most frequent pathotype was enteroaggregative E. coli . Isolated DEC presented high frequency of resistance to ampicillin (97.8%), tetracycline (68.3%), chloramphenicol (28.4%), nalidixic acid (19.5%), and gentamicin (14.4%). Conclusion: Children with diarrhea in Mozambique had DEC and higher resistance to ampicillin and tetracycline.